(untitled) (Experimental biology, 2021)
Soil invertebrates are bioindicators that characterize environmental changes due to high ecological and species diversity, close contact with the soil, high sensitivity and rapid response to changes in environmental parameters. This article presents the results of studies conducted in the biogeocenoses of the foothills of the beyond Ile Alatau in the period from 2018 to 2020. The parameters that affect the distribution and species composition of earthworms in various biogeocenoses are determined: soil moisture, organic matter index and pH of the environment. The family Lumbricidae is widely distributed in all biocenoses, although the predominant distribution is in the floodplain meadow. The humus content in the soils of this biocenosis is 3.26±0.30%, and the humidity is 14.56±2.58%. As a result of the study, 8 species of earthworms of the family Lumbricidae were identified, belonging to 5 genera: Octolasium lacteum, Eisenia foetida, Eisenia nordenskioldi, Nicodrilus caliginosus, Nicodrilus longus, Lumbricus rubellus, Lumbricus terrestris, Dendrobaena octaedra. The ratio of invertebrate groups in the soil varies throughout the season. Earthworms are found in the soils of biogeocenoses from June to September. Changes in environmental conditions contribute not only to the distribution and diversity of soil mesofauna, but also to their seasonal dynamics. Key words: soil mesofauna, earthworm, foothills of the beyond Ile Alatau, biogeocenosis, physical and chemical parameters.